2020
DOI: 10.3390/molecules25245815
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Alum-Containing Paper under Alkaline Conditions

Abstract: The present contribution evaluates the methods of degradation and stabilization of alum-containing paper with a focus on the alkaline environment achieved by deacidification procedures. In terms of reviewed subjects, the contribution focuses on alum-rosin sized paper, which is still used as a carrier of knowledge and information; however, it also mentions cellulose itself and other brands of paper. The contribution summarizes the results on the homogeneity of the distribution of alum and rosin in the paper mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Additionally, alum salts were used to reduce the absorbency of the paper, by depositing in the interstices of paper fibers, leading to better writing performance [ 21 ]. Interestingly, alum-treated papers are more susceptible to ageing, due to the increased acidity, which leads to the degradation of cellulose through acid-catalyzed hydrolysis [ 23 ]. Calcium-based compounds were used, among other reasons, to counteract and neutralize the acidity of alum-treated paper, thereby providing a protective effect [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, alum salts were used to reduce the absorbency of the paper, by depositing in the interstices of paper fibers, leading to better writing performance [ 21 ]. Interestingly, alum-treated papers are more susceptible to ageing, due to the increased acidity, which leads to the degradation of cellulose through acid-catalyzed hydrolysis [ 23 ]. Calcium-based compounds were used, among other reasons, to counteract and neutralize the acidity of alum-treated paper, thereby providing a protective effect [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…We can talk about a more significant stabilization of acid lignin-containing paper. The effectiveness of the stabilization process can be evaluated as the coefficient of the relative increase of the lifetime for observed properties, in this case folding endurance (S τ,ω ) [13,26,28]. It was determined as a linear regression of the logarithm of the folding endurance.…”
Section: Folding Endurancementioning
confidence: 99%
“…The effect of halogenides [8,9] and phenols [10] was also experimentally verified and studied. In this paper, we present a different approach: the introduction of multifunctional modification systems (MMS) [11][12][13], which allows us to solve the problem of documents, books, and other paper objects aging in a comprehensive mode, concerning ongoing degradation mechanisms (oxidation, acid hydrolysis) and consequences of degradation. In our previous work [10], we have dealt with the research and development of new stabilization systems of paper objects based on the latest knowledge from the world.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Al(III) ions, present in the paper due to alum-rosin sizing, responsible for increased acidity in the papers, are homogeneously dispersed throughout the paper mass, which is a consequence of the internal sizing of the paper (Jablonský and Šima 2020). Therefore, for the efficiency of deacidification, the distribution of alkaline compounds throughout the book paper matrix has been proven to be highly important (Buchanan et al 1994;Ahn et al 2012a).…”
Section: Distribution Of Mg-rich Particles On the Surface And In The ...mentioning
confidence: 99%